(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2012)
Analysis of burn mortality was done in Kasturba Medical College Hospital, Manipal. For that we retrospectively analysed hospital records of patients admitted in the burns ward of the Department of Plastic Surgery in Kasturba Medical College hospital from January 2005 to December 2010. Mortality was high in females (13.5%) as compared to males (6.6%). Highest mortality rate was in the age group of 51 to 60 years (41.2%), followed by 21–30 years (21.8%) and 11–20 years (21.1%). Burns involving more than 90% of total body surface area were invariably fatal, followed by 81–90% of total body surface area burnt and 71–80% of total body surface area burnt. Body surface area <10% and 11–20% had the least mortality rate (0%). Superficial burn (1.7%) has least mortality rate compared to deep burn (20.4%). Most of the deaths occurred in patients who sustained flame burns, followed by scald and electrical burns. Mortality rate was high in suicidal injuries, followed by homicidal injuries and accidental injuries. Most common cause of death was septicemia, which was seen in 45 cases (73.8%) followed by electrolyte imbalance, which was seen in 5 cases (8.2%).